2019
DOI: 10.25165/j.ijabe.20191205.5088
|View full text |Cite
|
Sign up to set email alerts
|

Performance of waterjet on cutting maize stalks: A preliminary investigation

Abstract: Large amounts of crop stalks left in the field as a result of conservation agriculture cause blockage during no-till planting. To solve this issue, pure waterjet was used to cut off the maize stalks so that the rear furrow opener could pass through without blockage. In this investigation, an experimental study on depth of cut, which was the main performance indicator of pure waterjet on cutting maize stalks, was presented. A full factorial design with 200 tests was implemented with respect to three operation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In this study, jet impingement angle was defined as the angle between the ground horizon plan and cutting head (as showed in Figure 1c), and adjustment range was 30°-90°. According to the previous study [20,21] , standoff distance should be less than 20 mm to decrease water steam diffusion and take full advantage of turbulence kinetic energy of waterjet. A parallelogram linkage also was designed to profile the ground and protect the cutting head from crashing soil clods and stubble on the ground.…”
Section: Materials and Methods 21 Materials 211 Equipment Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, jet impingement angle was defined as the angle between the ground horizon plan and cutting head (as showed in Figure 1c), and adjustment range was 30°-90°. According to the previous study [20,21] , standoff distance should be less than 20 mm to decrease water steam diffusion and take full advantage of turbulence kinetic energy of waterjet. A parallelogram linkage also was designed to profile the ground and protect the cutting head from crashing soil clods and stubble on the ground.…”
Section: Materials and Methods 21 Materials 211 Equipment Descriptionmentioning
confidence: 99%
“…In this study, a UHP waterjet was arranged to be the assisted component for maize stalk cutting, and the well-coordinated type of furrow opener was selected by evaluating the values of soil disturbance rate (SDR), stalks cutoff ratio (SCR), depth of soil cutting (DSC) and blockage degree. According to the previous preliminary study [20] and pilot tests, the values of operation parameters of waterjet pressure, jet impingement angle, and forward speed were selected as 260 MPa, 90° and 4 km/h, respectively. Experiment for each type of furrow opener was repeated three times with and without UHP waterjet assist, and the final value was the average of the three repetition measurements.…”
Section: Experimental Procedures 221 Experiments Setupmentioning
confidence: 99%
“…Moreover, when the wheat stem was wet and compressed, the water jet work efficiency was the highest. A full factorial design with 200 tests was implemented by Hu et al [74] to study the effect of different jet parameters on the cutting depth of one single corn stem. The experimental results showed that the cutting depth could increase with a high water jet pressure, a low traverse speed, and a short target distance.…”
Section: Anti-blockingmentioning
confidence: 99%
“…Third, many vegetables, fruits, and boneless meats can be cut at high target distances because of soft materials. It is necessary to increase the distance between the nozzle and the stem to avoid soil and stubble impacting the nozzle while working in the field [74]. Decreasing the target distance can reduce the volatilization of fertilizers [25].…”
Section: Comparison Of the Capability Of Water Jet Cutting The Above ...mentioning
confidence: 99%
“…The stalks of crops perform multiple physiological functions and encompass complex structural heterogeneity resulting in mechanical response variation under different conditions (Du and Wang, 2016). Lodging in cereal crops is mainly the result of interaction between plant character and external force.…”
Section: Introductionmentioning
confidence: 99%